PENGEMBANGAN SISTEM E-LEARNING BERBASIS WEB DI SMA XYZ - Agisfio, Muhammad Daffa (Universitas Lampung, 2026)
This study aims to develop a web-based e-learning system at SMA XYZ as a solution to address several problems, including limited access to learning materials, lack of interaction between teachers and students, and low administrative efficiency due to manual processes. The research employs the Waterfall development method, consisting of requirement analysis, system design, implementation, testing, and maintenance stages. The system design is based on the educational information system theory and the User-Centered Design (UCD) approach to create an intuitive and user-friendly interface tailored to user needs. Modeling tools such as Use Case Diagrams and Class Diagrams are used to map user interactions and data structures. The results show that the e-learning system developed using PHP and MySQL functions effectively, as demonstrated by functional testing (black box testing), which confirmed that all system features operate as intended. The system successfully enhances learning effectiveness, improves administrative efficiency, and strengthens teacher–student interaction in an online environment. Therefore, this web-based e-learning system is considered feasible to be implemented as a digital learning medium at SMA XYZ and has potential for further development through the integration of learning analytics features.